Knowledge Level of Multidrug Resistants Tuberculosis (MDR-TB) among Commuter Train Users - Rini Handayani; Cut Alia Keumala Muda; Namira Wadjir Sangadji (Alta Dharma Publisher, 2021)
Introduction: Multidrug Resistants Tuberculosis (MDR-TB) is biggest problem of preventive and elimination Tuberculosis (TB) Programmed in the world, include in Indonesia. It is more difficult when there are new strains of Mycobacterium tuberculosis which have resistant to Anti Tuberculosis Therapy (ATT). Objective: The aim of this study is to describe knowledge about MDR-TB on commuter train user in 2020 and its risk factors. Method: This research is observational study which used Cross sectional design study. The sample is 100 commuter train users who ?18 years old and use commuter train routine. The analysis was done in Chi-square test. Results: The result is 55% or 55 participants have bad knowledge about MDR-TB which the question that having less right answer are the meaning of MDR-TB (31%), diagnosis method of MDR-TB (33%), and the causes of MDR-TB (36%). It also showed there is relation of profession status (p-value: 0.019) and educational status (p-value: 0.044) with MDR-TB knowledge and there is no relation of age (p-value: 0.0227) and gender (p-value: 0.096) with MDR-TB knowledge. So, more than half of participants have bad knowledge of MDR-TB and the risk factors of MDR-TB Knowledge are profession status and educational status. Recommendation: To increase knowledge, it can do socialization of MDR-TB using short video and poster in each railway coach